Engineering human cell spheroids to model embryonic tissue fusion in vitro. - David G Belair; Cynthia J Wolf; Carmen Wood; Hongzu Ren; Rachel Grindstaff; William Padgett; Adam Swank; Denise MacMillan; Anna Fisher; Witold Winnik; Barbara D Abbott (PLoS ONE)
Epithelial-mesenchymal interactions drive embryonic fusion events during development, and perturbations of these interactions can result in birth defects. Cleft palate and neural tube defects can result from genetic defects or environmental exposures during development, yet very little is known about the effect of chemical exposures on fusion events during human development because of a lack of relevant and robust human in vitro assays of developmental fusion behavior. Given the etiology and prevalence of cleft palate and the relatively simple architecture and composition of the embryonic palate, we sought to develop a three-dimensional culture system that mimics the embryonic palate and could be used to study fusion behavior in vitro using human cells. We engineered size-controlled human Wharton's Jelly stromal cell (HWJSC) spheroids and established that 7 days of culture in osteogenesis differentiation medium was sufficient to promote an osteogenic phenotype consistent with embryonic palatal mesenchyme. HWJSC spheroids supported the attachment of human epidermal keratinocyte progenitor cells (HPEKp) on the outer spheroid surface likely through deposition of collagens I and IV, fibronectin, and laminin by mesenchymal spheroids. HWJSC spheroids coated in HPEKp cells exhibited fusion behavior in culture, as indicated by the removal of epithelial cells from the seams between spheroids, that was dependent on epidermal growth factor signaling and fibroblast growth factor signaling in agreement with palate fusion literature. The method described here may broadly apply to the generation of three-dimensional epithelial-mesenchymal co-cultures to study developmental fusion events in a format that is amenable to predictive toxicology applications.